Update on treatment of follicular non-Hodgkin’s lymphoma: focus on potential of bortezomib - Brander, Danielle M (Dove Medical Press, 2012)
Follicular lymphoma is predominantly managed as a chronic disease, with intermittent chemo/immunotherapy reserved for symptomatic progression. It is considered incurable with conventional treatments, and current therapeutic options are associated with significant toxicities that are especially limiting in older patients. Bortezomib (PS-341; Velcade(®)), a first-in-class drug targeting the proteolytic core subunit of the 26S proteasome, has emerged as a therapeutic alternative in follicular lymphoma, with promising preclinical data and efficacy in patients with other hematological malignancies. Several clinical trials were conducted with bortezomib for the treatment of non-Hodgkin’s lymphoma. As a single agent, overall responses in follicular lymphoma varied greatly (16%–41%), with weekly bortezomib showing less neurotoxicity than twice-weekly regimens, but with concern about decreased responses. Combination with rituximab was projected to improve the efficacy of bortezomib, but this resulted in increased toxicities and questionable added benefit. Although the largest Phase III study in follicular lymphoma of bortezomib plus rituximab versus rituximab alone demonstrated a significant progression-free survival difference, the absolute difference was small (12.8 months versus 11 months). Combining bortezomib with established regimens, such as rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP), rituximab, cyclophosphamide, vincristine, and prednisone (R-CVP), or rituximab-bendamustine also did not show definite benefit, and many of these studies did not meet their primary endpoint when bortezomib failed to improve responses or survival to the degree anticipated. In a disease where the goal of treatment is palliative and affected patients often have other medical and treatment-related comorbidities, decisions regarding therapies which carry risks of additional toxicities must be considered carefully. Conclusive evidence of the ability of bortezomib to improve patient outcomes meaningfully and to justify the added toxicity is lacking, but limitations in cross-trial comparisons are recognized. Large randomized trials and investigations of combinations with promising novel targeted agents will aid in determining the role of bortezomib, if any, in the future treatment of follicular lymphoma.